Polyphenol oxidases in plants and fungi: Going places? A review - Mayer, A.M.
The more recent reports on polyphenol oxidase in plants and fungi are reviewed. The main aspects considered are the structure, distribution, location and properties of polyphenol oxidase (PPO)as well as newly discovered inhibitors of the enzyme. Particular stress is given to the possible function of the enzyme. The cloning and characterization of a large number of PPOs is surveyed. Although the active site of the enzyme is conserved, the amino acid sequence shows very considerable variability among species. Most plants and fungi PPO have multiple forms of PPO. Expression of the genes coding for the enzyme is tissue specific and also developmentally controlled. Many inhibitors of PPO have been described, which belong to very diverse chemical structures; however, their usefulness for controlling PPO activity remains in doubt. The function of PPO still remains enigmatic. In plants the positive correlation between levels of PPO and the resistance to pathogens and herbivores is frequently observed, but convincing proof of a causal relationship, in most cases, still has not been published. Evidence for the induction of PPO in plants, particularly under conditions of stress and pathogen attack is considered, including the role of jasmonate in the induction process. A clear role of PPO in a least two biosynthetic processes has been clearly demonstrated. In both cases a very high degree of substrate specificity has been found. In fungi, the function of PPO is probably different from that in plants, but there is some evidence indicating that here too PPO has a role in defense against pathogens. PPO also may be a pathogenic factor during the attack of fungi on other organisms. Although many details about structure and probably function of PPO have been revealed in the period reviewed, some of the basic questions raised over the years remain to be answered.
Keywords: POLYPHENOL OXIDASE; STRUCTURE; GENES CODING; MULTIPLICITY; DISTRIBUTION; INDUCTION; PATHOGENS; HERBIVORES; INHIBITORS; FUNCTION OF ENZYME